Classical solutions of hyperbolic IBVPs with state dependent delays - Czernous, W. (Нелінійні коливання, 2010)
We consider the initial boundary-value problem for a system of quasilinear partial functional differential equations of the first order. Using the method of bicharacteristics and the fixed-point theorem we prove the local existence, uniqueness and continuous dependence on data of classical solutions of the problem.